Day 2 - 1550 - Rudi Hood.pdf - Gill, Philip (Cranfield University, 2023)
Thermal decomposition mechanism of nitrocellulose investigated by CHEMILUMINESCENCE Ian Wallace - Cranfield University Phil Gill - Roxel UK 9th International Nitrocellulose Symposium Presentations
Keywords: 'nitrocellulose'